NiCo nanotubes plated on Pd seeds as a designed magnetically recollectable catalyst with high noble metal utilisation. Issue 74 (22nd July 2016) - Schaefer, S.; Felix, E.-M.; Muench, F.; Antoni, M.; Lohaus, C.; Brötz, J.; Kunz, U.; Gärtner, I.; Ensinger, W.
Abstract : The tailored structure of a bifunctional, semi-homogeneous NiCo-nanotube catalyst system with embedded Pd nanoparticles, is synthesised by electroless plating. Abstract : Electroless plating of magnetic materials on catalytically active noble metal seeds is a powerful tool to design highly efficient recyclable catalysts. For the electroless plating procedure of metallic nanotubes in porous polymer templates, a sensitisation and activation process of the template is necessary. Therefore, metallic seeds are created on the surface of the polymer, which then enable the selective heterogeneous nucleation of a metal film on the template's surface. By choosing the metals for seeds and structures wisely, different functional materials can be purposefully combined. In this work magnetically recoverable catalysts were designed, which consist of magnetic NiCo nanotubes as carrier for catalytically active Pd seeds. The synthesised catalyst structures were thoroughly characterised by SEM, TEM, EDX, XRD, XPS, ICP-OES, VSM and then tested in the 4-nitrophenol reduction reaction, which was monitored by UV-Vis spectroscopy. After the reaction the structures were recycled and reused without a decrease in activity.